Brazil : The SOL-ution for Smart Community Procurement : Simple, Efficient, and Transparent Government Systems - World Bank (Washington, DC : World Bank, 2022)
SOL is the Portuguese acronym for Online Bidding Solution (Solução Online de Licitação). SOL is a GovTech solution for community-level procurements carried out under community-driven development (CDD) projects, and it addresses the procurement challenges that the communities usually face. Piloting SOL in selected projects in Brazil showed the app’s potential to increase the efficiency, transparency, and governance of the procurement process. The app facilitates the connection between community associations and their suppliers and automates the full procurement process. In addition, as all procurement data is generated and safely stored in the app, the app enhances the audit capacity of governments and the World Bank. Given the many positive results, SOL is to be upgraded with new features and translated into other languages to facilitate scale-up and use by other countries, including in Latin America and the Caribbean.